UPAYA MENINGKATKAN AKTIFITAS BELAJAR PPKn DENGAN MODEL PEER LESSON UNTUK SISWA SMP NEGERI 16 KABUPATEN TEBO - ELVITON ELVITON (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2022)
The aim of this research is; 1) describe the planning of Civics learning through the application of the Peer Lesson Learning Model in increasing the level of understanding of class VIII students, 2) describe the implementation of learning through the application of the Peer Lesson Learning Model in improving the learning activities of class VIII students, 3) describe the improvement of learning outcomes through the responses of class VIII students by applying the Peer Lesson Learning Model. The approach used is Classroom Action Research (CAR) through two learning cycles. The subjects in this study were students of class VIII-A of SMP Negeri 16 Tebo Regency, Jambi Province, for the 2019/2020 academic year with a total of 31 students. From the two learning cycles, the results of this study were able to achieve optimal results, it can be seen through student learning outcomes in cycle 1 the average value of students reached 57.60 and in Cycle 2 it became 78.40. Based on the results of the study, it turns out that the application of the Peer Lesson Learning Model can improve learning outcomes for Civics subjects for class VIII-A SMP Negeri 16 Tebo Regency, Jambi Province, for the 2019/2020 school year. ABSTRAKTujuan dari penelitian ini adalah; 1) mendeskripsikan perencanaan pembelajaran PPKn melalui penerapan Model Belajar Peer Lesson dalam meningkatkan tingkat pemahaman siswa kelas VIII, 2) mendeskripsikan pelaksanaan pembelajaran melalui penerapan Model Belajar Peer Lesson dalam meningkatkan aktifitas belajar siswa kelas VIII, 3) mendeskripsikan peningkatan hasil belajar melalui respon siswa kelas VIII dengan menerapkan Model Belajar Peer Lesson. Pendekatan yang digunakan adalah Penelitian Tindakan Kelas (PTK) melalui dua siklus pembelajaran. Subjek dalam penelitian ini adalah Siswa kelas VIII-A SMP Negeri 16 Kabupaten Tebo Provinsi Jambi tahun pelajaran 2019/2020 dengan jumlah 31 orang siswa. Dari dua siklus pembelajaran, hasil dari penelitian ini mampu mencapai hasil yang optimal, hal tersebut terlihat melalui hasil belajar siswa pada siklus 1 rata-rata nilai siswa mencapai 57,60 dan pada Siklus 2 menjadi 78,40. Berdasarkan hasil penelitian, ternyata penerapan Model Belajar Peer Lesson dapat meningkatkan hasil belajar mata pelajaran PPKn kelas VIII-A SMP Negeri 16 Kabupaten Tebo Provinsi Jambi tahun pelajaran 2019/2020.